Lies he told me - Patterson, James, 1947-; Ellis, David, 1967- (Little Brown and Company, 2024)
"An attorney and mother of two discovers her husband's secret life - and it might cost them all their lives. Everyone in Hemingway Grove, Illinois, knows David and Marcie Bowers. David owns the local pub. Marcie is a former big-city lawyer who practices family law. When David jumps into Cotton River to save a drowning stranger, he's celebrated as a hero. His muscled physique, shaved head, and piercing blue eyes are broadcast on every news outlet. For most people, newfound fame is a lifeline. For David Bowers, it's a death sentence. For Marcie Bowers, it's a test. A wife knows the difference between a loving husband and father and a cold-blooded assassin. Right?"--